夏季北冰洋楚科奇海微微型、微型浮游植物和细菌的丰度分布特征及其与水团的关系 - 张芳; 何剑锋; 郭超颖; 林凌; 马玉欣 (2012)
利用2008年中国第三次北极科学考察的机会,分析夏季楚科奇海微微型、微型浮游植物和细菌丰度的分布特征,并探讨它们与楚科奇海水团之间的关系。结果表明:与北冰洋的其他海域相比,楚科奇海的微型浮游植物丰度相对较高(0.03—10.23x103CEllS·Ml-1),微微型浮游植物则大致相同(0.01—2.21x103CEllS·Ml-1),而浮游细菌丰度明显较高(0.21—9.61x106CEllS·Ml-1)。白令海陆架水与海冰融化混合水和阿纳德尔水浮游植物群落结构不同,夏季随着太平洋水入流水对楚科奇海的日益影响,其水体本身的群落结构可能被外来群落替代。 Based on the third Chinese Arctic Expedition cruise in the summer of 2008,the distribution patterns of pico-and nano-plankton and bacterial abundances were studied in the Chukchi Sea.Pico-and nano-phytoplankton abundances ranged from 0.01×103 to 5.51×103 cells·mL-1 and from 0.01×103 to 5.51×103 cells·mL-1,respectively.The lowest numbers of bacteria in the entire water column were recorded at station R17 at 100 m depth(0.21×106 cells·mL-1),and the highest concentration was observed at station R09 at 10 m depth(9.61×106 cells·mL-1).Our results demonstrate that melting sea ice affects the physical characteristics of the Chukchi Sea by reducing the salinity of the surface mixed layer which,in turn,results in greater hydrodynamic stability of the water column.These changes were accompanied by increasing bacterial concentrations.Pacific warm water brought high nutrient concentrations into the Chukchi Sea,which led to higher abundances of bacteria and nano-phytoplankton compared to other regions of the Arctic Ocean.However,the number of pico-phytoplankton in the Anadyr Water related well to chlorophyll a,and the number was greater than those in the other two water masses.The structure of pico-and nano-plankton communities,coupled with the water masses in the Chukchi Sea,can be considered indicators of the inflow of Pacific warm water into the Chukchi Sea. 国家自然科学基金(41076130;40576002);科技部国际合作司对欧盟科技合作专项经费项目(1105);国家海洋局青年海洋科学基金项目(2010116)资助